Explaining the declining utilization of village clinics in rural China over time: A decomposition approach - Yunwei Chen; Sean Sylvia; Paiou Wu; Hongmei Yi (Social Science & Medicine, 2022)
With a goal of improving health system quality and efficiency, reforms of China's health system over the past decade have sought to strengthen primary healthcare in lower-level clinics and health centers. Despite these wide-ranging reforms and initiatives, population-based studies have documented dramatic declines in patients' use of primary care facilities during this period. In this paper, we explore the determinants of this trend in China's rural areas using detailed longitudinal data following a nationally-representative sample of rural households and village clinics from 2011 to 2018. We estimate that between 2011 and 2018, the probability that individuals sought care at village clinics when ill dropped by 44%. At the same time, the utilization of outpatient services in county hospitals increased by 56% and patient self-treatment increased by 20%. Detailed Kitagawa-Oaxaca-Blinder decompositions suggest four primary drivers of this trend: the shifting burden of disease in rural areas, changes in how patients choose to seek care given different disease conditions, declining drug inventory in village clinics, and the decreasing importance of remoteness as a determinant of healthcare seeking behavior. Our results highlight the deteriorating role of village clinics in the rural healthcare system and the increasing importance of self-treatment and higher-tier primary care services.